Effect of vacancy defects on electronic structure and ferromagnetism in pristine In2O3 nanostructures: An experimental study and first-principles modeling. (August 2022) - Dhamodaran, Manikandan; Murugan, Ramaswamy; Boukhvalov, Danil W.; Karuppannan, Ramesh; Vediyappan, Sivasubramani; Pandian, Muthu Senthil; Perumalsamy, Ramasamy
Highlights: Single-phase In2 O3 nanorods and nanoparticles prepared by hydrothermal-annealing method. HRTEM analysis revealed the change in morphology from rectangular rod to nanoparticles. Most energetically favorable stable (111) and (001) surfaces of the In2 O3 were investigated via DFT. A theoretical model was proposed to understand the coexistence of observed RTFM and electronic structure. The origin of observed RTFM was related to the increased number of intrinsic defects. Abstract: Single-phase In2 O3 cubic crystal structure nanorods and nanoparticles with defined morphology and microstructure were prepared by the hydrothermal method followed by an annealing process. High-resolution transmission electron microscopy analysis indicated the formation of In2 O3 rectangular nanorods and spherical nanoparticles. Magnetic measurements revealed room temperature ferromagnetism in the prepared samples, which could be correlated to the increased number of intrinsic defects, especially dangling bonds on corners and edges of nanorods and nanoparticles. First-principles modeling established these In2 O3 nanoparticles as a system of ferromagnetic clusters of large spins connected by a network of weak ferromagnetic interactions via indium vacancies on the (111) surface. A theoretical model was proposed to explain the coexistence of room temperature ferromagnetism and semiconductive electronic structure in In2 O3 nanostructures. The present study provides new evidence and insight into vacancy defect-mediated ferromagnetism. Graphical abstract: The formation of vacancy defects mediate the room temperature ferromagnetism and electronic structure modulation in the prepared In2 O3 nanorods and nanoparticles Image, graphical abstract .